Assessment Practices in Constructivist Paradigm at the Higher Secondary level in Kerala - S., Jayalekshmi; Pereira, Celine (JOURNAL OF INDIAN EDUCATION, 2013)
The purpose of the study is to bring out innovative practices in assessment at the Higher Secondary Level. This study is aimed at developing the principles of assessment that suits the needs of the students of higher secondary classes and identifying the learning-teaching processes, the method of assessment (both formative and summative) and the procedure for recording the assessment results from the point of view of a specific context. A survey method was conducted by using the tools such as questionnaire, interview schedule and Focus Group Discussion points. The population consists of teachers, students and principals of higher secondary schools of Kerala. The sample consists of 50 teachers of commerce, 500 students of commerce and 10 principals of higher secondary schools. Observations regarding the study are that the commerce teachers themselves experimented in real classrooms on selected themes in business studies subject in selected schools. The relationship of learning outcomes, assessment task and assessment criteria were clearly established. The findings of the study proved that the principles of assessment developed to suit the needs of higher secondary students in Kerala context is very appropriate and the methods of assessment and its recording are effective and practicable at the higher secondary level according to critical pedagogy and constructivist approach.